EDUKASI MASYARAKAT TENTANG KESEHATAN MELALUI PEMBUATAN DETERGEN BERBASIS BAHAN ALAM DI KABUPATEN KUBU RAYA - Naniek Tri Utami; Sofi Siti Shofiyah; Irma Ramadhani Febriaty; Weni Mandasari; Yulizar Prawiranti (LPPM Universitas Abdurrab, 2025)
Detergent is one of the essential needs in achieving good hygiene standards, which in turn can improve public health. The use of natural ingredients, such as pandan and lime, has great potential to have a positive impact on the health of the community Kubu Raya. This PKM program on making natural ingredient-based detergents aims to improve the community's knowledge and skills regarding health, especially in the use of natural ingredient-based household cleaning products. The PKM implementation method involves lectures, training, and discussions. In these activities, resource persons delivered presentations to the community, provided hands-on training on how to make detergent using pandanus and lime leaves, and conducted interactive discussions. The discussion included a question-and-answer session between participants and resource persons, as well as a quiz with prizes for participants who could demonstrate an understanding of the material presented. The target audience of this PKM program is the community of Kubu Raya Regency, 20 people participated in this activity. The evaluation results showed an increase in participants' understanding of the ingredients for making natural-based detergents, as well as their motivation to make and sell these detergents.